Kevin S. answered • 02/04/13

The vertex (h,k) is (0,0) and the focus (h, k+p) is (0,-3/10). Since k+p = -3/10 and k = 0, p = -3/10

We can now use the formula (y - k) = (1/4p) (x - h)^{2} and plug in what we know:

y - 0 = [1/4(-3/10)](x - h)^{2}

y = [(1/4(-3/10)]x^{2} = (1/4)(-10/3)x^{2} = -10/12x^{2} = -5/6 x^{2}

**y = (-5/6)x ^{2}** is the equation of the parabola. and it opens down.

Since the focus is (0,-3/10) and the vertex is (0,0), the distance from the vertex to the directrix is

|0 - (-3/10)| or 3/10, which makes the directrix y = 3/10.

The axis of symmetry is x = 0